Effects of Trans-4-Aminomethylcyclohexane Carboxylic Acid as an Antifibrinolytic Agent on Arterial Wall and Experimental Atherosclerotic Lesions in Rabbits - Kato, N; Morimatsu, M; Tanaka, K; Horie, A (Thrombosis and Haemostasis, 1970)
Effects of trans-4-aminomethylcyclohexane carboxylic acid (t-AMCHA) as an antifibrinolytic agent on the experimental arteriosclerosis produced by cholesterol feeding and on the experimental thromboembolism induced by autogenous fibrin clot injection were observed in rabbits. Effect of inhibited fibrinolysis on the arterial wall itself was also observed.Administration of 500 mg/kg body weight of t-AMCHA highly inhibited the lysis time of serum, but there was no influence on the plasma fibrinogen level.There was no significant difference in the cholesterol level, sudanophilia of the aorta and the accumulation of foam cells in the aorta and pulmonary arteries between t-AMCHA + cholesterol group and cholesterol group.Edema in the subendothelial layer of the aorta and elastic pulmonary artery, proliferation and swelling of the endothelial cells, and edema of the subendothelial layer of large muscular pulmonary arteries were increased in the incidence and severity in t-AMCHA treated animals. Localized intimai fibrous thickening was found in large muscular artery in t-AMCHA treated animals. Small fibrin thrombi and angitis were rarely found in muscular pulmonary artery in t-AMCHA treated animals.Fibrinolytic activity of blood and dissolution of clots in the pulmonary arteries were depressed by t-AMCHA treatment in the animals injected autogenous fibrin clots, while the inflammatory reaction in the arterial wall was less severe as compared with that of untreated animals.It was reasonable to presume that the inhibition of fibrinolysis would promote the development of atherosclerosis through its influence on the fibrin dissolution on and in the arterial wall, and on the vascular permeability of the arterial wall.